Analysis of sildenafil citrate in male stamina herbal medicines from the Magelang region, Central Java using thin-layer chromatography and UV spectrophotometry - Saputra, Ilham Fahmi; Haresmita, Perdana Priya; Dianita, Puspita Septie; Kholifah, Eva (Acta Pharmaciae Indonesia, 2024)
Background: Male stamina herbal medicines are widely consumed in Indonesia, often believed to enhance sexual performance. However, the illegal addition of medicinal chemicals (BKOs) such as sildenafil citrate in traditional herbal products poses health risks. Objective: To identify and quantify sildenafil citrate in selected herbal medicine samples using thin-layer chromatography (TLC) and UV spectrophotometry. Method: Three samples of male stamina herbal medicine were purchased and subjected to organoleptic tests. Ethanol (96%) was used for extraction, followed by TLC analysis using two mobile phases (methanol: chloroform at 4:1 and 1:1 ratios). UV spectrophotometry was employed to determine the maximum absorbance wavelength and quantify sildenafil citrate. Results: TLC analysis revealed that two samples (K and L) contained sildenafil citrate, with Rf values consistent with the standard. UV spectrophotometry confirmed the presence of sildenafil citrate at a maximum wavelength of 292.5 nm. Sample K contained 0.96%, while sample L had 13.766% sildenafil citrate. Conclusion: The presence of sildenafil citrate in two samples violates Indonesian regulations prohibiting medicinal chemicals in herbal products, raising significant safety concerns.